The Rise of Mob Justice: Causes, Consequences, and Remedies in the Light of Law and Islamic Shari’ah (Jagannath University Journal of Arts, 2026)
Mob justice, the act of a crowd taking the law into their own hands to punish alleged offenders without legal due process, has become an alarming phenomenon in some part of the world. This article explores the underlying causes of mob violence, including social disorganization, weak law enforcement, and public mistrust in the justice system. Through statistical analysis and case examples, the paper reveals the extent and severity of mob justice incidents in recent years. It critically examines the legal implications, highlighting the violation of fundamental human rights under both the Constitution of Bangladesh and international law. Furthermore, the article provides an in-depth analysis of Islamic teachings, illustrating how mob justice contravenes core principles of Shari‟ah, which emphasizes due process, fairness, and state authority in administering justice. The views of classical scholars and contemporary Islamic legal bodies reinforce the condemnation of vigilantism. Finally, the paper proposes remedial measures, including legal reforms, public awareness, and socio-economic interventions, aimed at eradicating mob justice and upholding the rule of law in line with both civil and Islamic jurisprudence.Jagannath University Journal of Arts, v-5, i-01, 2025: p144-152